Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau de santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

L’offre active des services de santé et de mieux‑être en français au Nouveau‑Brunswick - Société Santé en français et les Réseaux de santé en français

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)